Augmenting photosynthesis through facile AIEgen-chloroplast conjugation and efficient solar energy utilization. Issue 5 (26th April 2021) - Bai, Haotian; Liu, Haixiang; Chen, Xu; Hu, Rong; Li, Meng; He, Wei; Du, Jian; Liu, Zhiyang; Qin, Anjun; Lam, Jacky W Y; Kwok, Ryan T K; Tang, Ben Zhong
Abstract : Two new AIE molecules with activated alkyne groups were successfully conjugated with live chloroplasts by a facile metal-free "Click" reaction, and the formed artificial AIEgen-chloroplast owned the increased photosynthetic activity. Abstract : Photosynthesis is regarded as the foundation for sustaining life on our planet. Light-harvesting is the initial step that activates the subsequent photochemical reactions. In the photosystems, chloroplast is the basic light-driven metabolic factory of higher plant cells. However, there is an incomplete match between the solar radiation spectrum and absorption profile of chloroplasts. It is hard for the photosynthetic pigments to fully utilize the sunlight energy. Here, we designed two new aggregation-induced emission (AIE) molecules with activated alkyl groups (TPE-PPO and TPA-TPO). Via a facile metal-free "Click" reaction, we realized the substantial manipulation of live chloroplasts with the AIE luminogens (AIEgens). Owing to the matched photophysical properties, the AIEgens could harvest harmful ultraviolet radiation (HUVR) and photosynthetically inefficient radiation (PIR), and further convert them into photosynthetically active radiation (PAR) for chloroplast absorption. As a result, the conjugated AIEgen-chloroplast exhibited better capability of water splitting and electron separation. It promoted the generation of adenosine triphosphate (ATP), which is an important product of photosynthesis. This work provides an effective strategy for improving plant photosynthesis.